PENGARUH LINGKUNGAN TEMPAT TINGGAL DAN DISIPLIN BELAJAR TERHADAP HASIL BELAJAR GEOGRAFI SISWA KELAS XI SMAN 1 TANJUNG MUTIARA - Andira Sari, Afrilia; Ahmad, Ridwan; Zuriyani, Elvi (Pendidikan Geografi, 2013)
TheÂ  pupose from this research is to determine the extentÂ  of the influence of the neigborhood and the discipline of learning to learn geography for students clas XI SMAN 1 Tanjung Mutiara. The kind of this research is descriptive corelation. The population from this research is students class XI SMAN 1 Tanjung Mutiara all totaled 185 students to determine the sample size used sampling technicques performed by simple rando sampling using slovin formula. The total sample of 127 students. Data collection technique used is descriptive analytical and to the test the hypotesis used multiple regression F test and T test. Results of this indicate theit: (1) sigificant relationship between living environment on learning outcomes of geography students class XI SMAN 1 Tanjung Mutiara about 13,5 % (percent).(2) A significant difference between of the discipline of learning outcomes of geography students class XI SMAN 1 Tanjung Mutiara by 9,8 % (percent). (3) A significant diference